The effect of electronic service quality on customer satisfaction A field study on Syrital customers on the Syrian coast - زاهر بسام (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The research aimed to identify the degree of impact of electronic service quality on the satisfaction of Syrital customers in the Syrian coast by focusing on four dimensions of electronic service quality, which are reliability, ease of use, interactivity, and design. The results of the research indicated that there is a significant effect for each dimension of electronic service quality represented by reliability, ease of use, interactivity, and design on the satisfaction of Syrital customers in the Syrian coast. The most important recommendations of the research were the necessity for the company under study to work continuously to provide electronic services with a high degree of efficiency, strive to achieve zero errors, and interact effectively with customers’ electronic requests 24 hours a day, 7 days a week, designing electronic services in an innovative and attractive way so that they effectively influence customers through the use of sensory marketing techniques and neuromarketing techniques.